Segmentation of cracks in shale rock - Urbach, E.; Pervukhina, Marina; Bischof, L. (na, 2011)
In this paper the use of morphological connected filters are studied for segmenting sheet- and thread-like cracks in images of shale rock. A volume formed from a stack of 2-D X-ray images is processed using 3-D attributes. The shape-preserving property of these filters provides accurate segmentation results while the use of rotation-invariant attributes allow robust and computationally efficient segmentation of cracks at all orientations. The results obtained using shape and size attributes are provided and discussed. The research presented here is part of a project with geologists to provide tools for automated segmentation and analysis of features of interest in various types of rock. © 2011 Springer-Verlag.